Thermoplastic resin particles and method for manufacturing three-dimensional objects by powder bed fusion using the same
Bimodal thermoplastic resin particles with optimized size ratios and high tap density address the issues of voids and density in 3D printing, achieving high-strength, void-free models with enhanced fluidity and filling properties.
Patent Information
- Application Number
- JP2021028426
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-25
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-02-25
AI Technical Summary
Existing thermoplastic resin particles used in powder bed fusion bonding methods for 3D printing face challenges in achieving high particle filling rates and fluidity, leading to issues with void formation and density in the resulting models.
The use of bimodal thermoplastic resin particles with specific particle size ratios (S2/S1 between 0.10 and 0.45) and high tap density (0.6 to 0.9) ensures both high particle filling rates and excellent fluidity, minimizing voids and enhancing the density of the modeled objects.
This approach results in high-density, void-free 3D models with improved fluidity and filling properties, enabling the production of high-strength objects with precise details.
Smart Images

Figure 0007613153000001 
Figure 0007613153000002 
Figure 0007613153000003
Abstract
Description
[Technical field]
[0001] The present invention relates to thermoplastic resin particles and a method for producing a three-dimensional object by powder bed fusion using the same. [Background technology]
[0002] Powder bed fusion is known as a 3D printing technology for manufacturing three-dimensional objects (hereinafter, sometimes referred to as "modeled objects"). In this method, after providing a layer of thermoplastic resin particles, a laser is selectively irradiated at a position corresponding to the cross section of the object to melt the thermoplastic resin particles, and the layers of thermoplastic resin particles are bonded and laminated together. In addition, an electromagnetic radiation absorber or suppressor is printed at a position corresponding to the cross section, and selectively absorbs thermal energy such as infrared rays to melt the thermoplastic resin particles, and the layers of thermoplastic resin particles are bonded and laminated together to form a three-dimensional object (hereinafter, sometimes referred to as "modeling"). This method has the advantage of being able to model high-strength resin compared to other methods for creating three-dimensional objects, and in recent years, there has been an increasing trend to utilize models obtained by this method as final products.
[0003] In this context, there is an increasing demand for high-strength molded objects, and in order to obtain such objects, it is important to prevent the formation of voids that cause defects inside the objects. In other words, when forming layers of thermoplastic resin particles, it is necessary to prepare particles that are layered at a high density so that as little gas as possible remaining in the gaps between the raw thermoplastic resin particles remains in the molded object.
[0004] In response to the above problem, Patent Document 1 discloses bimodal particles made of an amorphous resin having a first D50 (a particle size at which the cumulative curve from the small particle size side is 50%) of less than 1 mm and a D50 of 0.414 times the first D50, and claims that the highly packed particles can prevent undesired voids. Patent Document 2 discloses a resin powder of 30 μm to 100 μm, including resin particles with a primary particle size of 1.50 μm or less, and claims that the generation of internal voids during lamination can be prevented. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6552727 [Patent Document 2] JP 2020-189965 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, Patent Document 1 describes two particle size ratios that theoretically result in high packing, but does not take into account interactions such as interparticle adhesive force, etc. In other words, generally, the higher the particle packing, the lower the fluidity tends to be, and although the particle packing rate is high, there is an issue with fluidity.
[0007] In addition, in Patent Document 2, fine resin particles are used as a lubricant to prevent static electricity and to exhibit excellent fluidity. However, the density of the stacked particles has not been sufficiently considered, and the particle packing rate has not been sufficiently increased.
[0008] Therefore, an object of the present invention is to provide thermoplastic resin particles that have a high particle packing rate and excellent fluidity in order to obtain a highly packed object in three-dimensional modeling by powder bed fusion. [Means for solving the problem]
[0009] In order to solve the above problems, the thermoplastic resin particles used in the powder bed fusion method of the present invention are as follows: D50 particle size is 10μm or more and 100μm or less Spherical thermoplastic resin particlesThe volumetric particle size distribution is bimodal, and when the mode diameter of the larger peak in the volumetric particle size distribution is S1 and the mode diameter of the smaller peak is S2, S2 / S1 is 0.10 or more and 0.45 or less, and the tap density of the thermoplastic resin particles divided by the true density of the resin constituting the thermoplastic resin particles is 0.72 Thermoplastic resin particles, characterized in that the molecular weight is greater than or equal to 0.9.
[0010] The method for producing a three-dimensional object of the present invention is a method for producing a three-dimensional object by a powder bed fusion method using the thermoplastic resin particles. Effect of the Invention
[0011] The present invention aims to provide thermoplastic resin particles that have a high particle packing rate and excellent fluidity in order to obtain highly packed objects in three-dimensional modeling using powder bed fusion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below.
[0013] In the powder bed fusion molding method, a layer of thermoplastic resin particles, which is the raw material, is formed, and then the particles at the position corresponding to the cross section of the desired object are melted and welded by a heat source. When forming a layer of thermoplastic resin particles, gas is always present in the gaps between the particles, so in order to obtain a high-density object without voids, the gas needs to be discharged from the system when melting and welding. However, in conventional thermoplastic resin particles, the density is low when filled, and a relatively large amount of gas is present when a layer of thermoplastic resin particles is formed, so the gas cannot be completely discharged when melting and welding, and voids exist in the obtained object, and the density is lower than the true density of the thermoplastic resin raw material. In response to this, a method is known in which the above-mentioned thermoplastic resin particles, that is, bimodal particles made of a particle having a first D50 of less than 1 mm and an amorphous resin having a D50 0.414 times the first D50, are closely packed to minimize voids in the particle state. In addition, it is said that the particles can prevent unwanted voids in the object by highly packed particles.
[0014] However, in a randomly mixed particle system, the ideal close-packed structure does not form. In addition, the higher the packing ratio, the lower the powder flowability, making it difficult to form a uniform layer of thermoplastic resin particles. For this reason, it was not possible to achieve both good thermoplastic resin particle layer forming properties (powder spreading properties) and high-density molded objects.
[0015] As a result of extensive research into this issue, the inventors discovered that thermoplastic resin particles having a bimodal peak at a specific particle size ratio and a high tap density combine good fluidity (spreadability) with high filling properties, and that the use of these particles makes it possible to obtain high-density molded objects.
[0016] In other words, the thermoplastic resin particles used in the powder bed fusion method of the present invention are thermoplastic resin particles for producing three-dimensional objects by the powder bed fusion method, characterized in that the volumetric particle size distribution is bimodal, and when the mode diameter of the larger peak in the volumetric particle size distribution is S1 and the mode diameter of the smaller peak is S2, S2 / S1 is 0.1 or more and 0.45 or less, and the value obtained by dividing the tap density of the thermoplastic resin particles by the true density of the resin that constitutes the thermoplastic resin is 0.6 or more and 0.9 or less.
[0017] The powder bed fusion method in the present invention is a 3D printing method in which a layer of thermoplastic resin particles, which is a raw material, is formed, and the position corresponding to the cross section of the desired object is melted and welded by a heat source, and a layer of thermoplastic resin particles is further formed on the layer, and this operation is repeated to obtain a three-dimensional object. In this case, electromagnetic radiation is preferably used as the heat source, and more preferably coherent electromagnetic radiation (so-called laser light) is used. When non-coherent light such as a halogen lamp is used as the electromagnetic radiation, a light energy absorber or a light energy absorption inhibitor may be printed at a position corresponding to the cross section of the desired object to efficiently utilize the energy of the electromagnetic radiation. The light energy absorber is a substance that absorbs electromagnetic radiation. Examples of such substances include carbon black, carbon fiber, copper hydroxyphosphate, near infrared absorbing dyes, near infrared absorbing pigments, metal nanoparticles, polythiophene, poly(p-phenylene sulfide), polyaniline, poly(pyrrole), polyacetylene, poly(p-phenylene vinylene), polyparaphenylene, poly(styrene sulfonate), poly(3,4-ethylenedioxythiophene)-poly(styrene phosphonate) p-diethylaminobenzaldehyde diphenylhydrazone, or conjugated polymers consisting of combinations thereof, which may be used alone or in combination. The light energy absorption inhibitor is a substance that does not easily absorb electromagnetic radiation. Examples of such substances include substances that reflect electromagnetic radiation such as titanium, heat insulating powders such as mica powder and ceramic powder, and water, which may be used alone or in combination. These light energy absorbers or light energy absorption inhibitors may be used alone or in combination. In the step of printing the light energy absorbent or the light energy inhibitor into a shape corresponding to the cross-sectional shape of the desired shaped object, a known method such as inkjet printing can be used. In this case, the light energy absorbent or the light energy absorption inhibitor may be used as it is, or may be used after being dispersed or dissolved in a solvent.
[0018] The thermoplastic resin particles in the present invention are spherical or nearly spherical particles made of a thermoplastic resin. Here, known thermoplastic resins can be used as needed. Specific examples include polycarbonate, polyacetal, polyester, polysulfone, polyarylate, polyurethane, polyamide, polyarylene sulfide, polyphenylene sulfide, polyamideimide, polyetheretherketone, polyetherimide, polyethersulfone, and other polyethers, polyethylene, polypropylene, vinyl polymers such as polymethyl methacrylate, and alloys and copolymers thereof. Among them, in the powder bed fusion method, crystalline thermoplastic resin particles are preferred because precise shaped objects can be obtained by shaping at a temperature above the crystallization temperature and below the melting point of the thermoplastic resin used, and polyacetal, polyester, polyetheretherketone, polyamide, polyurethane, polyphenylene sulfide, polyethylene, and polypropylene are preferred. Polyether, polyester, polyamide, polyphenylene sulfide, and polyamideimide are more preferred because of their excellent solvent resistance, polyester, polyamide, polyphenylene sulfide, and polyether ether ketone are even more preferred because they have excellent heat resistance and can be molded with a general-purpose 3D printer, and polyamide is the most preferred because of its excellent toughness. These may be used alone or in combination. For example, different types of thermoplastic resins may be copolymerized, may be alloyed in the particles, or particles of different thermoplastic resins may be mixed.
[0019] The polyester in the present invention is a polymer containing an ester bond in the repeating structure, and is obtained by polycondensation of a polybasic acid or a polybasic acid dialkyl ester and a polyhydric alcohol as main raw materials.Specific examples of polyesters include polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polycyclohexane dimethylene terephthalate, polyhexylene terephthalate, polyethylene naphthalate, polypropylene naphthalate, polybutylene naphthalate, polyethylene isophthalate / terephthalate, polypropylene isophthalate / terephthalate, polybutylene isophthalate / terephthalate, polyethylene terephthalate / naphthalate, polypropylene terephthalate / naphthalate, polybutylene terephthalate / naphthalate, polybutylene terephthalate / decane dicarboxylate, polyethylene terephthalate / cyclohexane dimethylene terephthalate, polyethylene terephthalate / polyethylene glycol, polypropylene terephthalate / polyethylene glycol, polybutylene terephthalate / polyethylene glycol, polyethylene terephthalate / polytetramethylene glycol, polypropylene terephthalate / polytetramethylene glycol, polybutylene terephthalate / polytetramethylene glycol, polyethylene Polyethylene terephthalate / isophthalate / polytetramethylene glycol, polypropylene terephthalate / isophthalate / polytetramethylene glycol, polybutylene terephthalate / isophthalate / polytetramethylene glycol, polyethylene terephthalate / succinate, polypropylene terephthalate / succinate, polybutylene terephthalate / succinate, polyethylene terephthalate / adipate, polypropylene terephthalate / adipate, polybutylene terephthalate / adipate, polyethylene terephthalate / sebake polypropylene terephthalate / sebacate, polybutylene terephthalate / sebacate, polyethylene terephthalate / isophthalate / adipate, polypropylene terephthalate / isophthalate / adipate, polybutylene terephthalate / isophthalate / succinate, polybutylene terephthalate / isophthalate / adipate, polybutylene terephthalate / isophthalate / sebacate, bisphenol A / terephthalic acid, bisphenol A / isophthalic acid, bisphenol A / terephthalic acid / isophthalic acid, and the like.
[0020] Among these polyester resins, polybutylene terephthalate resin (PBT resin) is preferably used. PBT resin is composed of 80% by weight or more, preferably 85% by weight or more of polybutylene terephthalate, and may be copolymerized or mixed with other resins other than PBT resin.
[0021] The polyamide in the present invention is a polymer containing an amide bond in the repeating structure. Such polyamides are produced by known methods such as polycondensation reaction of amino acids, anionic ring-opening polymerization of lactams and an initiator, cationic ring-opening polymerization or ring-opening polymerization after hydrolysis with water, polycondensation reaction of dicarboxylic acids and diamines or their salts, or a combination of these. Specific examples of such polyamides include polyamide 4, polyamide 5, polyamide 6, polyamide 8, polyamide 11, polyamide 12, polyamide 44, polyamide 46, polyamide 410, polyamide 411, polyamide 412, polyamide 56, polyamide 510, polyamide 511, polyamide 512, polyamide 64, polyamide 65, polyamide 66, polyamide 610, polyamide 611, polyamide 612, polyamide 104, polyamide 106, polyamide 1010, polyamide 1011, polyamide 1012, polyamide 124, polyamide 125, polyamide 126, polyamide 1210, polyamide 1212, polyamide 6T, polyamide 10T, polyamide 12T, polyamide 6I, polyamide 10I, polyamide 12I, and further copolymers of these polyamides, such as polyamide 6 / polyamide 66 copolymer. Since they can be produced relatively inexpensively, polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 66, polyamide 610, polyamide 612, polyamide 106, polyamide 1010, polyamide 1011, polyamide 1012, polyamide 1212, polyamide 6T, polyamide 6I, or a copolymer consisting of a combination selected from these are preferred. From the viewpoint of having a melting point and crystallization temperature suitable as a material for 3D printers, polyamide 6, polyamide 11, polyamide 12, polyamide 66, polyamide 1010, polyamide 1012, polyamide 1212, polyamide 6T, polyamide 6I, or a copolymer consisting of a combination selected from these are more preferred.From the viewpoint of achieving an excellent balance between elastic modulus and toughness, polyamide 6, polyamide 12, polyamide 66, polyamide 1010, polyamide 1012, polyamide 6T, polyamide 6I, or a copolymer consisting of a combination selected from these are more preferable, and from the viewpoint of achieving excellent solvent resistance, polyamide 6, polyamide 12, polyamide 66, polyamide 6T, polyamide 6I, or a copolymer consisting of a combination selected from these are particularly preferable, with polyamide 6 being most preferable.
[0022] The polyamide may contain other copolymerizable components as long as the invention is not impaired. The copolymerizable components may be appropriately selected from elastomer components such as polyolefins and polyalkylene glycols that impart flexibility, and rigid aromatic components that improve heat resistance and strength. The polyamide may also be end-blocked with substances such as benzoic acid, hexanoic acid, terephthalic acid, isophthalic acid, benzylamine, aniline, hexylamine, p-diaminobenzene, and m-diaminobenzene.
[0023] The thermoplastic resin particles of the present invention may contain antioxidants, heat stabilizers, weather resistance agents, lubricants, pigments, dyes, plasticizers, antistatic agents, flame retardants, flow modifiers, etc., for the purpose of improving the moldability, improving the heat resistance of the particles, and improving the heat resistance, flame retardancy, and weather resistance of the molded product. Two or more of these may be used in combination.
[0024] Examples of such antioxidants include organic antioxidants such as phenols, amines, sulfurs, lactones, and phosphites, and inorganic salt-based antioxidants such as copper salts such as copper chloride, copper bromide, copper iodide, copper acetate, copper acetylacetonate, copper carbonate, copper borofluoride, copper citrate, copper hydroxide, copper nitrate, copper sulfate, and copper oxalate, and manganese salts. Commercially available antioxidants containing these as the main component may also be used as appropriate.
[0025] Examples of such flame retardants include nitrogen-based flame retardants such as melamine cyanurate, metal hydroxide flame retardants such as magnesium hydroxide and aluminum hydroxide, phosphorus-based flame retardants such as ammonium polyphosphate, melamine polyphosphate, metal phosphinates and red phosphorus, and halogen-based flame retardants such as brominated polystyrene, brominated polyphenylene oxide, brominated polycarbonate and brominated epoxy resin. Commercially available flame retardants containing these as the main component may be used as appropriate.
[0026] As such flow improvers, fatty acid metal salts are preferably used, and examples thereof include capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, and melissic acid.
[0027] Furthermore, the thermoplastic resin particles in the present invention may contain a lubricant to improve fluidity. Examples of such lubricants include silica (silicon dioxide) such as fused silica, crystalline silica, and amorphous silica, alumina (aluminum oxide), alumina colloid (alumina sol), and alumina white, calcium carbonate such as light calcium carbonate, heavy calcium carbonate, finely powdered calcium carbonate, and special calcium carbonate-based fillers, nepheline syenite fine powder, calcined clay such as montmorillonite and bentonite, clay (aluminum silicate powder) such as silane-modified clay, silicic acid-containing compounds such as talc, diatomaceous earth, and silica sand, crushed natural minerals such as pumice powder, pumice balloon, slate powder, and mica powder, barium sulfate, litho Examples of the filler include minerals such as porcelain, calcium sulfate, molybdenum disulfide, and graphite, glass fillers such as glass fibers, glass beads, glass flakes, and foamed glass beads, fly ash spheres, volcanic glass hollow bodies, synthetic inorganic hollow bodies, single crystal potassium titanate, carbon nanotubes, carbon hollow spheres, fullerenes, anthracite powder, artificial cryolite, titanium oxide, magnesium oxide, basic magnesium carbonate, dolomite, potassium titanate, calcium sulfite, mica, asbestos, calcium silicate, molybdenum sulfide, and thermosetting resin fine particles such as melamine resin and benzoguanamine resin. More preferred are silica, alumina, calcium carbonate powder, and titanium oxide. Particularly preferred are silica and alumina, which are hard and contribute to improving strength.
[0028] Commercially available examples of such silica include the fumed silica "AEROSIL" (registered trademark) series manufactured by Nippon Aerosil Co., Ltd., the dry silica "Reolosil" (registered trademark) series manufactured by Tokuyama Corporation, and the sol-gel silica powder X-24 series manufactured by Shin-Etsu Chemical Co., Ltd.
[0029] The average particle size of the lubricant is preferably 20 nm or more and 1 μm or less. The upper limit of the average particle size of the lubricant is preferably 1 μm, more preferably 500 nm, more preferably 400 nm, particularly preferably 300 nm, and most preferably 200 nm. The lower limit is preferably 20 nm, more preferably 30 nm, more preferably 50 nm, and particularly preferably 100 nm. If the average particle size of the lubricant is within the above range, the fluidity of the thermoplastic resin particles can be improved and the lubricant can be uniformly dispersed in the thermoplastic resin particles.
[0030] The average particle size of the lubricant in the present invention is the particle size (D50 particle size) at which the cumulative curve from the small particle side becomes 50% when the cumulative curve is calculated with the total volume of the microparticles obtained by analyzing scattered light from a laser by dynamic light scattering method as 100%.
[0031] The amount of the lubricant is preferably more than 0.01 parts by mass and less than 5 parts by mass with respect to 100 parts by mass of the thermoplastic resin particles. The upper limit of the amount is preferably 3 parts by mass or less, more preferably 1 part by mass or less, even more preferably 0.5 parts by mass or less, particularly preferably 0.3 parts by mass or less, and extremely preferably 0.1 parts by mass or less. The lower limit of the amount is preferably more than 0.02 parts by mass, more preferably more than 0.03 parts by mass, and even more preferably more than 0.04 parts by mass. If the amount of the lubricant is more than 0.01 parts by mass, the flowability of the thermoplastic resin particles is further improved, and the filling property when molded is increased, so that voids that become defects in mechanical properties are less likely to occur, and the molded product obtained exhibits high strength. If the amount of the lubricant is less than 5 parts by mass, the lubricant does not cover the surface of the thermoplastic resin particles, thereby preventing sintering, and a molded product with high strength can be obtained.
[0032] The range of the weight-average molecular weight of the resin constituting the thermoplastic resin particles in the present invention is preferably 8,000 or more and 300,000 or less. If the weight-average molecular weight is less than 8,000, the physical properties of the manufactured object may be poor, so the weight-average molecular weight is preferably 8,000 or more, more preferably 10,000 or more, even more preferably 30,000 or more, and extremely preferably 40,000 or more. If the weight-average molecular weight exceeds 300,000, the viscosity is too high when the particles are melted and fused, so that the particles do not fuse together well, so the weight-average molecular weight is preferably 300,000 or less, more preferably 200,000 or less, and even more preferably 150,000 or less.
[0033] The range of the molecular weight distribution of the thermoplastic resin in the present invention is preferably 3.0 or less, more preferably 2.5 or less, and even more preferably 2.0 or less, from the viewpoint of suppressing the formation of undesired voids during molding. The lower limit is 1 by definition.
[0034] In the present invention, the weight average molecular weight refers to the weight average molecular weight measured by gel permeation chromatography using hexafluoroisopropanol as a solvent and converted into polymethyl methacrylate. If the thermoplastic resin is not soluble in hexafluoroisopropanol, the value measured by dissolving it in pentafluorophenol is used. The molecular weight distribution refers to the weight average molecular weight measured by gel permeation chromatography and converted into polymethyl methacrylate divided by the number average molecular weight.
[0035] The thermoplastic resin particles in the present invention are characterized by a bimodal volumetric particle size distribution. The volumetric particle size distribution is a distribution of particle sizes weighted by volume, and the bimodal volumetric particle size distribution means that when the particle size distribution is plotted on a coordinate system with particle size on the horizontal axis and volumetric frequency on the vertical axis, the graph has two maximum values. The particle size distribution of the thermoplastic resin particles can be measured by a laser diffraction particle size distribution meter. In the present invention, when the particle size of the larger peak in the volumetric particle size distribution graph is S1 and the particle size of the smaller peak is S2, S2 / S1 is 0.10 or more and 0.45 or less. When S2 / S1 exceeds 0.45, the thermoplastic resin particles are not sufficiently packed, and the purpose of obtaining a high-density molded object cannot be achieved. In order to improve the packing rate, S2 / S1 is preferably 0.4 or less, more preferably 0.35 or less, and even more preferably 0.30 or less. When S2 / S1 is less than 0.10, the thermoplastic resin particles are not sufficiently packed, and a high-density molded product cannot be obtained. In order to improve the packing rate, S2 / S1 is preferably 0.15 or more, and more preferably 0.20 or more.
[0036] The particle diameter S1 of the larger peak of the thermoplastic resin particles in the present invention is preferably 30 μm or more and 120 μm or less. If S1 exceeds 120 μm, when forming a layer of thermoplastic resin particles by the powder bed fusion method, the thickness of the layer cannot be made thin, and a highly detailed molded object tends not to be obtained. From the viewpoint of obtaining a more detailed molded object, S1 is preferably 100 μm or less, more preferably 80 μm or less. Also, if S1 is less than 30 μm, fine particles increase in the entire thermoplastic resin particles, so aggregation is likely to occur and the fluidity is reduced, and the layer of thermoplastic resin particles may not be formed well. From the viewpoint of suppressing the occurrence of aggregation, S1 is preferably 40 μm or more, more preferably 50 μm or more.
[0037] The particle size S2 of the smaller peak of the thermoplastic resin particles in the present invention is preferably 5 μm or more and 40 μm or less. If S2 is larger than 40 μm, the amount of coarse particles increases in the entire thermoplastic resin particles, and when a layer of the thermoplastic resin particles is formed by the powder bed fusion method, the thickness of the layer cannot be made thin, and a highly detailed molded object cannot be obtained. From the viewpoint of obtaining a highly detailed molded object, it is preferably 30 μm or less. If S2 is smaller than 5 μm, the thermoplastic resin particles are likely to aggregate, the fluidity is reduced, and the layer of the thermoplastic resin particles cannot be formed well. From the viewpoint of suppressing the occurrence of aggregation, S2 is preferably 10 μm or more, more preferably 15 μm or more.
[0038] The thermoplastic resin particles in the present invention preferably have a D50 particle size of 10 μm or more and 100 μm or less. When the D50 particle size is 10 μm or less, fine particles increase in the entire thermoplastic resin particles, which makes it easy for aggregation to occur and reduces fluidity, so that a layer of thermoplastic resin particles may not be formed well. From the viewpoint of suppressing the occurrence of aggregation, the D50 particle size is preferably 20 μm or more, more preferably 30 μm or more. When the D50 particle size is larger than 100 μm, when forming a layer of thermoplastic resin particles by the powder bed fusion method, the layer thickness cannot be thinned, and a highly detailed molded object may not be obtained. From the viewpoint of obtaining a highly detailed molded object, the D50 particle size is preferably 70 μm or less, more preferably 60 μm or less.
[0039] In addition, in the present invention, the D10 particle size is preferably 1 μm or more and 30 μm or less. When the D10 particle size is less than 1 μm, the thermoplastic resin particles are likely to aggregate and the fluidity is reduced, so that the layer of the thermoplastic resin particles may not be formed well. From the viewpoint of suppressing the occurrence of aggregation, the D10 particle size is preferably 3 μm or more, more preferably 5 μm or more. When the D10 particle size is 30 μm or more, the number of coarse particles increases in the entire plastic resin particles, so that when a layer of the thermoplastic resin particles is formed by the powder bed fusion method, the thickness of the layer cannot be thinned, and a highly fine molded object cannot be obtained. From the viewpoint of obtaining a highly fine molded object, the D10 particle size is preferably 25 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. When the D10 particle size is less than 1 μm, the thermoplastic resin particles are likely to aggregate and the fluidity is reduced, so that the layer of the thermoplastic resin particles may not be formed well. From the viewpoint of suppressing the occurrence of aggregation, the D10 particle size is preferably 3 μm or more, more preferably 5 μm or more.
[0040] Furthermore, in the present invention, the D90 particle size is preferably 50 μm or more and 120 μm or less. When the D90 particle size is 120 μm or more, the number of coarse particles increases, so when a layer of thermoplastic resin particles is formed by the powder bed fusion method, the thickness of the layer cannot be made thin, and a highly detailed molded object may not be obtained. From the viewpoint of obtaining a highly detailed molded object, the D90 particle size is preferably 100 μm or less, and more preferably 90 μm or less. When the D90 particle size is less than 50 μm, fine particles increase in the entire thermoplastic resin particles, so aggregation is likely to occur and the fluidity is reduced, and the layer of thermoplastic resin particles may not be formed well. From the viewpoint of suppressing the occurrence of aggregation, the D90 particle size is preferably 55 μm or more, and more preferably 60 μm or more.
[0041] The D10, D50, and D90 particle sizes of the thermoplastic resin particles are the particle sizes at which the cumulative frequency from the small particle size side of the particle size distribution measured by a laser diffraction particle size distribution meter is 10%, 50%, and 90%, respectively.
[0042] In the volumetric particle size distribution of the thermoplastic resin particles of the present invention, when the frequency of particle size S1 is F1 and the frequency of particle size S2 is F2, it is preferable that F2 / F1 is 0.15 or more and 2 or less. When it is in this range, it is easy to achieve both the packing property and the fluidity of the particles. As the lower limit, F2 / F1 is more preferably 0.2 or more, and as the upper limit, it is more preferably 1 or less, and further preferably 0.75 or less.
[0043] The thermoplastic resin particles of the present invention are characterized in that the tap density of the thermoplastic resin particles divided by the true density of the resin constituting the thermoplastic resin particles is 0.6 or more and 0.9 or less. When a layer of thermoplastic resin particles is formed in the powder bed fusion method, the particles are compressed and close to a tapped state. Therefore, in order to obtain a high-density molded object, the packing rate in the tapped state, that is, the value divided by the true density of the resin constituting the thermoplastic resin particles (tap packing rate) is important. Thermoplastic resin particles having a value divided by the true density of the resin constituting the thermoplastic resin particles of 0.6 or more and 0.9 or less are packed at a sufficiently high density to reduce the porosity of the molded object, and good fluidity (powder spreadability) is also ensured. When the tap density of the thermoplastic resin particles divided by the true density of the resin constituting the thermoplastic resin particles is less than 0.6, the particle packing rate of the layer of thermoplastic resin particles formed during molding in the powder bed fusion method is insufficient, and the voids in the target molded object cannot be sufficiently reduced. On the other hand, when the value obtained by dividing the tap density of the thermoplastic resin particles by the true density of the resin constituting the thermoplastic resin particles is greater than 0.9, the filling property is too high, and sufficient fluidity for forming a layer of the thermoplastic resin particles cannot be ensured. From the viewpoint of reducing voids in the molded object, the value obtained by dividing the tap density of the thermoplastic resin particles by the true density of the resin constituting the thermoplastic resin particles is preferably 0.65 or more, more preferably 0.7 or more, and even more preferably 0.75 or more, and from the viewpoint of increasing the fluidity of the thermoplastic resin particles, it is preferably less than 0.85.
[0044] The tap density of the thermoplastic resin particles indicates the mass per unit volume when the powder is gently filled into a container and then densely packed by tapping, and is measured in accordance with the Japanese Industrial Standards (JIS) JIS K 7370 (2000) "Determination of Packed Apparent Bulk Density". The true density of the resin constituting the thermoplastic resin particles is measured in accordance with the Japanese Industrial Standards (JIS) JIS Z 8807 (2012) "Method of Measurement of Density and Specific Gravity of Solids".
[0045] The present invention is also characterized in that the Hausner ratio, which is the value obtained by dividing the tap bulk density of the thermoplastic resin particles by the apparent bulk density, is 1 or more and 1.5 or less. Here, the apparent bulk density refers to the mass per unit volume when the thermoplastic resin particles are filled in a container. Here, the apparent bulk density is measured according to the Japanese Industrial Standards (JIS) JIS K 7365 (1999) "Method of determining the apparent density of a material that can be poured from a specified funnel". In general, the value obtained by dividing the tap bulk density by the apparent bulk density is called the Hausner ratio, which is an index of the fluidity of a powder, and the smaller the value, the higher the fluidity. In principle, the tap bulk density cannot be smaller than the apparent bulk density, so the lower limit of the value obtained by dividing the tap bulk density of the thermoplastic resin particles by the apparent bulk density is 1. If the value obtained by dividing the tap bulk density of the thermoplastic resin particles by the apparent bulk density exceeds 1.5, the fluidity is low, and a layer of the thermoplastic resin particles cannot be formed neatly. From the viewpoint of obtaining a fine surface of the obtained shaped article, the ratio is preferably 1.3 or less, more preferably 1.25 or less, and even more preferably 1.2 or less.
[0046] The sphericity of the thermoplastic resin particles in the present invention is preferably 80 or more. The sphericity is a value expressed by 100×minor diameter / major diameter, where the longest diameter (major diameter) of a particle and the largest diameter (minor diameter) perpendicular to the major diameter, when the particle is observed by an electron microscope or the like. That is, the closer this value is to 100, the more spherical the shape is, and the maximum value is 100 according to the calculation method. From the viewpoint that the closer to a spherical shape, the better the flowability, the sphericity of the thermoplastic resin particles is more preferably 85 or more, even more preferably 90 or more, and particularly preferably 95 or more.
[0047] The thermoplastic resin particles in the present invention preferably have a smooth surface because this improves fluidity. Surface smoothness can be evaluated by the linseed oil absorption of the particles per unit weight. That is, the smoother the surface, the less uneven the particles are, and the lower the linseed oil absorption, which indicates the amount of linseed oil absorbed. The linseed oil absorption of the polyamide microparticles of the present invention is preferably 100 mL / 100 g or less, more preferably 80 mL / 100 g or less, even more preferably 70 mL / 100 g or less, and particularly preferably 60 mL / 100 g or less. The lower limit of the linseed oil absorption is 0 mL / 100 g by definition. The linseed oil absorption is measured in accordance with JIS K 5101 "Pigment Test Method - Refined Linseed Oil Method" of the Japanese Industrial Standards (JIS). Surface smoothness can also be expressed by the BET specific surface area by gas adsorption, and the smoother the surface, the smaller the BET specific surface area. Specifically, the BET specific surface area is 10 m 2 / g or less, and more preferably 5m 2 / g or less, and more preferably 3m 2 / g or less, and particularly preferably 1m 2 / g or less, and most preferably 0.5m 2 / g or less. The lower limit of the BET specific surface area is 0 m 2 The BET specific surface area is measured in accordance with the Japanese Industrial Standards (JIS) R1626 (1996) "Method of measuring specific surface area by gas adsorption BET method."
[0048] The thermoplastic resin particles in the present invention can be prepared by mixing thermoplastic resin particles having two different particle size distributions. The respective thermoplastic resin particles before mixing may be produced by any method, and any existing method can be used. Examples of such methods include a method of physically pulverizing a thermoplastic resin prepared in advance, a chemical pulverization method in which a solution in which a thermoplastic resin prepared in advance is dissolved in a good solvent is cooled or added to a poor solvent to precipitate as a powder, a kneading method in which a thermoplastic resin constituting the thermoplastic resin particles and a resin that is incompatible with the thermoplastic resin are melt-kneaded to form a sea-island structure, and then the sea phase is dissolved, an emulsion method in which an emulsion in which a solution in which a thermoplastic resin constituting the thermoplastic resin particles is dissolved in a good solvent is used as a dispersed phase, and then particles are precipitated, a method in which a molten thermoplastic resin or a thermoplastic resin dissolved in a good solvent is melt-kneaded to form an island-in-sea structure, and then the sea phase is dissolved, and then the particles are precipitated. Examples of such methods include the atomization method, in which a plastic resin is atomized by spraying to produce particles; suspension polymerization, in which a water-insoluble monomer or a solution of a monomer is dispersed in an aqueous medium and polymerized; emulsion polymerization, in which micelles are formed in an aqueous medium using a surfactant or the like, and polymerized and granulated inside the micelles; precipitation polymerization, in which a monomer is soluble in a solvent but a polymer is insoluble in the solvent, is polymerized in a medium in which the monomer is soluble, but the polymer is insoluble; seed polymerization, in which a seed particle is absorbed by a monomer and then the particle size is enlarged by polymerization; and a method in which polymerization is performed in a polymer medium that is compatible with the monomer but not with the polymer, and polymer particles are precipitated after the polymerization is completed. Since spherical particles with a particle size of about 1 to 300 μm can be obtained simultaneously with the polymerization, a method in which polymerization is performed in a polymer medium that is compatible with the monomer but not with the polymer, and polymer particles are precipitated after the polymerization is completed is preferable. After producing thermoplastic resin particles by these methods, the particle size distribution may be appropriately adjusted using a particle separator such as a sieve. In addition, commercially available particles may be purchased and mixed before mixing, and further crushing, classification, etc. may be performed appropriately before mixing.
[0049] When the thermoplastic resin particles in the present invention are produced by mixing thermoplastic resin particles having two different particle size distributions, each of the thermoplastic resin particles may have any chemical composition as long as the desired chemical composition is obtained after mixing.
[0050] In the present invention, when the thermoplastic resin particles are produced by mixing two different types of thermoplastic resin particles having different particle size distributions, the D50 particle size of the thermoplastic resin particles before mixing is 5 μm or more and 120 μm or less. If it is out of this range, the particle size distribution of the thermoplastic resin particles after mixing does not fall within the target range. It is preferably 10 μm or more and 100 μm or less.
[0051] In the present invention, when the thermoplastic resin particles are produced by mixing two different types of thermoplastic resin particles having different particle size distributions, the volume-based particle size distribution of the thermoplastic resin particles before mixing is preferably monodisperse, from the viewpoint of easily controlling the particle size distribution of the thermoplastic resin particles after mixing. The volume-based particle size distribution being monodisperse means that when the particle size distribution is plotted on a coordinate system with particle size on the horizontal axis and volume-based frequency on the vertical axis, the graph has one maximum value.
[0052] In the present invention, when the thermoplastic resin particles are produced by mixing two different types of thermoplastic resin particles having different particle size distributions, the particle size distribution index of the thermoplastic resin particles before mixing is preferably 3.0 or less, more preferably 2.5 or less, and the lower limit is theoretically 1. Here, the particle size distribution index is the value obtained by dividing the volume average particle size measured by a laser diffraction particle size distribution meter by the number average particle size.
[0053] In the present invention, when the thermoplastic resin particles are produced by mixing thermoplastic resin particles having two different particle size distributions, from the viewpoint of improving the fluidity of the thermoplastic resin particles after mixing, the sphericity is preferably 80 or more, more preferably 85 or more, even more preferably 90 or more, and most preferably 95 or more. The upper limit of the sphericity is 100 by definition.
[0054] When the thermoplastic resin particles in the present invention are produced by mixing thermoplastic resin particles having two different particle size distributions, it is preferable that the surface is smooth from the viewpoint of improving the fluidity of the thermoplastic resin particles after mixing.
[0055] In the present invention, when the thermoplastic resin particles are prepared by mixing two different types of thermoplastic resin particles having different particle size distributions, any existing method such as dry blending or wet blending can be selected as the method for mixing the particles. Examples of the dry blending method include a container rotation type and a container fixed for stirring. As a container rotation type mixer, any shape such as a horizontal cylinder type, an inclined cylinder type, a V-shape, a double cone type, a regular cube type, an S-shape, or a continuous V-shape can be selected according to the particle properties. As a mixer for stirring with a fixed container, a ribbon type, a screw type, a rod type, or a combination of these with stirring blades can be selected, and a horizontal or vertical rotation axis can be selected as desired. In addition, mixers such as a vibration mill and a vibration sieve can be used, and a combination of these mixing methods can be used. Furthermore, mixing may be performed by a wet method, and a method of preparing a slurry with a medium such as water in which the thermoplastic resin particles do not dissolve, homogenizing the whole using a mixing device such as a screw, and then drying can be used.
[0056] Furthermore, within the scope of the present invention, when mixing the thermoplastic resin particles having two different particle size distributions or after mixing, a lubricant for improving flowability, an antioxidant, a heat stabilizer, a weather resistance agent, a lubricant, a pigment, a dye, a plasticizer, an antistatic agent, a flame retardant, a flow modifier, and the like may be additionally added. EXAMPLES
[0057] The present invention will be described below based on examples, but the present invention is not limited to these.
[0058] [Measurement method] In the examples, the measurements used are as follows:
[0059] (1) Apparent bulk density, tapped bulk density, and Hausner ratio of thermoplastic resin particles The apparent density of the thermoplastic resin particles was measured according to the Japanese Industrial Standards (JIS) Z 7365 (1999) by dropping 50 g of thermoplastic resin particles into a funnel at 100 cm 3 The volume was read and the weight of the polymer powder was divided by the volume. The tap density of the thermoplastic resin particles was determined by dropping 50 g of thermoplastic resin particles into a funnel at 100 cm according to the Japanese Industrial Standards (JIS) Z 7370 (2000). 3 The volume of the thermoplastic resin particles was read after tapping and the weight of the thermoplastic resin particles was divided by the volume. The tapped bulk density was then divided by the apparent bulk density to obtain the Hausner ratio.
[0060] (2) True density of thermoplastic resin particles The true density of the thermoplastic resin particles was calculated according to the Japanese Industrial Standards (JIS) JIS Z 8807 (2012) by placing approximately 10 g of polymer powder and a solvent with a smaller specific gravity than the polymer powder in a Gay-Lussac-type pycnometer, measuring the weights of the pycnometer only, the pycnometer powder, the pycnometer + powder + solvent, and the pycnometer + solvent, and using the following formula:
[0061]
number
[0062] Here, d: true density of powder, d0: density of solvent, Wa: weight of pycnometer, Wb: weight of pycnometer + powder, Wc: weight of pycnometer + powder + solvent, Wd: weight of pycnometer + solvent.
[0063] (3) Tap filling rate The tap bulk density obtained by the method (1) was calculated from the true density of the resin obtained by the method (2) according to Equation 2, and this was taken as the tap filling rate.
[0064]
number
[0065] In addition, Pr is the tapped filling rate, Dtap is the tapped bulk density, and Dpolym is the true density of the resin.
[0066] (4) D10, D50, D90 particle size and mode diameter of thermoplastic resin particles A dispersion of about 100 mg of thermoplastic resin particles dispersed in about 5 mL of deionized water was added to a laser diffraction particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Nikkiso Co., Ltd. until a measurable concentration was reached. After ultrasonic dispersion for 60 seconds at 30 W in the analyzer, the particle sizes at which the cumulative frequency from the small particle size side of the particle size distribution measured in a measurement time of 10 seconds was 10%, 50%, and 90% were defined as the D10, D50, and D90 particle sizes, respectively. The particle size showing the most frequent value was defined as the mode diameter. The refractive index during measurement was 1.52, and the refractive index of the medium (deionized water) was 1.333.
[0067] (5) Sphericity of thermoplastic resin particles The sphericity of the thermoplastic resin particles was calculated from the minor axis and major axis of 30 randomly selected particles observed in a scanning electron microscope (JSM-6301NF, manufactured by JEOL Ltd.) according to the following mathematical formula 3.
[0068]
number
[0069] In addition, S: sphericity, a: major axis, b: minor axis, and n: 30 (number of measurements).
[0070] (6) Linseed oil absorption of thermoplastic resin particles In accordance with the Japanese Industrial Standards (JIS) K 5101 "Pigment test method - refined linseed oil method," approximately 100 mg of thermoplastic resin particles was precisely weighed out on a watch glass, refined linseed oil (Kanto Chemical Co., Ltd.) was gradually added drop by drop using a burette, and the mixture was kneaded with a palette knife. The dropping and kneading were repeated until a sample mass was formed, and the end point was the point at which the paste became smooth and hard. The oil absorption (mL / 100 g) was calculated from the amount of refined linseed oil used for dropping.
[0071] (7) Crystallization temperature and melting point of thermoplastic resin particles Using a TA Instruments differential scanning calorimeter (DSCQ20), the temperature was raised once in a nitrogen atmosphere from 30°C to a temperature 30°C higher than the endothermic peak indicating the melting point of the polymer at a heating rate of 20°C / min, held for 1 minute, and then lowered to 30°C at 20°C / min and held for 1 minute. This refers to the apex of the endothermic peak associated with melting and the exothermic peak associated with crystallization. Approximately 8 mg of polymer powder was required for the measurement.
[0072] (8) Molecular weight of the thermoplastic resin constituting the thermoplastic resin particles The weight average molecular weight of the polyamide was calculated by gel permeation chromatography in comparison with a calibration curve of polymethyl methacrylate. The measurement sample was prepared by dissolving about 3 mg of polyamide fine particles in about 3 g of hexafluoroisopropanol. Instrument: Waters e-Alliance GPC system Column: Showa Denko HFIP-806M x 2 Mobile phase: 5mmol / L sodium trifluoroacetate / hexafluoroisopropanol Flow rate: 1.0mL / min Temperature: 30℃ Detection: Differential refractometer.
[0073] (9) Porosity of the object Using a Sartorius precision balance (CP225D) and a specific gravity / density measurement kit (YDK01), calculations were made according to Equation 4. The densities of water and air were corrected according to temperature in accordance with the Chemistry Handbook.
[0074]
number
[0075] where Ds is the density of the object, Wa is the weight of the object in air, Ww is the weight of the object in water, Pw is the density of water, and Pa is the density of air.
[0076] [Preparation of particle 1] In a 3L autoclave, 360g of ε-caprolactam (special grade reagent, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 240g of polyethylene glycol (1st grade polyethylene glycol 6,000, manufactured by Wako Pure Chemical Industries, Ltd.), 2.5g of IRGANOX1098 (manufactured by BASF Japan Ltd.) as an antioxidant, and 50g of deionized water were added and sealed, and the process of pressurizing with nitrogen to 1MPa and releasing the pressure to 0.1MPa was repeated three times, and the inside of the container was replaced with nitrogen, after which the pressure was adjusted to 0.1MPa and the container was sealed. Then, the stirring speed was set to 62 rpm and the temperature was raised to 230°C. At this time, the pressure in the system was 1.4 MPa, and stirring was continued at 62 rpm for 3 hours while maintaining the pressure and temperature. Next, the pressure was released at a rate of 0.2 MPa·min, and the internal pressure was set to 0 MPa. Then, the polymerization temperature was set to 210°C, and nitrogen was flowed at a rate of 5 L / min to perform polymerization for 1 hour. Finally, the mixture was discharged into a 2000g water bath to obtain a slurry. After the slurry was thoroughly homogenized by stirring, it was filtered, 2000g of water was added to the filter cake, and it was washed at 80°C. The slurry liquid from which the aggregates were removed by passing it through a 100μm sieve was filtered again, and the isolated filter cake was dried at 80°C for 12 hours to obtain polyamide 6 particles. The melting point of the obtained polyamide 6 particles was 217°C, the crystallization temperature was 173°C, and the weight average molecular weight was 35,000. The mode diameter was 54μm, D90 / D10 was 2.5, the sphericity was 96, and the linseed oil absorption was 35mL / 100g. The true density of the resin was measured and found to be 1.13.
[0077] [Preparation of particle 2] Except for changing the stirring speed to 32 rpm, the same granulation process as for Particle 1 was carried out to obtain polyamide 6 particles. The melting point of the obtained polyamide 6 particles was 218°C, the crystallization temperature was 174°C, and the weight average molecular weight was 32,000. The mode diameter was 70 μm, the D90 / D10 was 2.7, the sphericity was 93, and the linseed oil absorption was 26 mL / 100 g. The true density of the resin was measured and found to be 1.13.
[0078] [Preparation of particle 3] Except for changing the stirring speed to 85 rpm, the same granulation process as for Particle 1 was carried out to obtain polyamide 6 particles. The melting point of the obtained polyamide 6 particles was 215°C, the crystallization temperature was 172°C, and the weight average molecular weight was 39,000. The mode diameter was 23 μm, the D90 / D10 was 2.6, the sphericity was 93, and the linseed oil absorption was 55 mL / 100 g. The true density of the resin was measured and found to be 1.13.
[0079] [Preparation of particle 4] Except for changing the stirring speed to 90 rpm, the same granulation process as for particle 1 was carried out to obtain polyamide 6 particles. The melting point of the obtained polyamide 6 particles was 216°C, the crystallization temperature was 170°C, and the weight average molecular weight was 46,000. The mode diameter was 23 μm, the D90 / D10 was 2.5, the sphericity was 98, and the linseed oil absorption was 60 mL / 100 g. The true density of the resin was measured and found to be 1.13.
[0080] [Preparation of particle 5] Polyamide 6 particles were obtained by granulation in the same manner as for Particles 1, except that the stirring speed was set to 100 rpm. The mode diameter of the obtained polyamide 6 particles was 10 μm, and the sphericity was 95. The true density of the resin was measured and found to be 1.13.
[0081] [Preparation of particle 6] Polyamide 6 particles were obtained by granulation in the same manner as for particles 1, except that the stirring speed was set to 73 rpm. The mode diameter of the obtained polyamide 6 particles was 35 μm and the sphericity was 93. The true density of the resin was measured and found to be 1.13.
[0082] [Preparation of particle 7] Polyamide 6 particles were obtained by granulation in the same manner as for Particles 1, except that the stirring speed was set to 25 rpm. The mode diameter of the obtained polyamide 6 particles was 92 μm, and the sphericity was 90. The true density of the resin was measured and found to be 1.13.
[0083] [Example 1] 1500g of the prepared particle 1 and 250g of particle 4 were thoroughly mixed in a mortar, and the mixture was passed through a 300μm mesh sieve three times to make the whole homogenous. 5.3g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) with an average particle size of 170nm was added as a lubricant, and the whole was further mixed and passed through a 300μm mesh sieve three times to make the whole homogenous. The particle size distribution of the mixed particles thus obtained was measured to be bimodal, with the particle sizes of the respective peaks being 70μm and 15μm. The sphericity of the mixed particles was 95. The bulk density of the mixed particles was measured to find that the apparent bulk density was 0.70 and the tapped bulk density was 0.86, and the Hausner ratio calculated from these was 1.23, and the tapped filling rate was calculated to be 0.76.
[0084] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.125, and the porosity of the model was 0.5%. The properties are shown in Table 1.
[0085] [Example 2] Mixed particles were prepared in the same manner as in Example 1, using 1200 g of the prepared particles 1, 400 g of particles 4, and 4.8 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 70 μm and 15 μm. The sphericity of the mixed particles was 97. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.74 and a tapped bulk density of 0.91. The Hausner ratio calculated from these was 1.23, and the tapped filling rate was calculated to be 0.81.
[0086] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.127, and the porosity of the model was 0.3%. The properties are shown in Table 1.
[0087] [Example 3] Mixed particles were prepared in the same manner as in Example 1, using 1000 g of the prepared particles 1, 500 g of particles 4, and 4.5 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 70 μm and 15 μm. The sphericity of the mixed particles was 97. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.65 and a tapped bulk density of 0.81, with the Hausner ratio calculated from these being 1.25 and the tapped filling rate being calculated to be 0.72.
[0088] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.122, and the porosity of the model was 0.7%. The properties are shown in Table 1.
[0089] [Example 4] Mixed particles were prepared in the same manner as in Example 1, using 1500 g of the prepared particles 1, 250 g of particles 3, and 5.3 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 70 μm and 23 μm. The sphericity of the mixed particles was 94. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.68 and a tapped bulk density of 0.81, with the Hausner ratio calculated from these being 1.19 and the tapped filling rate being calculated to be 0.72.
[0090] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.120, and the porosity of the model was 0.9%. The properties are shown in Table 1.
[0091] [Example 5] Mixed particles were prepared in the same manner as in Example 1, using 1200 g of the prepared particles 1, 400 g of particles 3, and 4.8 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 70 μm and 23 μm. The sphericity of the mixed particles was 94. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.69 and a tapped bulk density of 0.83, with the Hausner ratio calculated from these being 1.20 and the tapped filling rate being calculated to be 0.73.
[0092] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.121, and the porosity of the model was 0.8%. The properties are shown in Table 1.
[0093] [Example 6] Mixed particles were prepared in the same manner as in Example 1, using 1500 g of the prepared particles 2, 250 g of particles 4, and 5.3 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 54 μm and 15 μm. The sphericity of the mixed particles was also 95. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.63 and a tapped bulk density of 0.84, with the Hausner ratio calculated from these being 1.33 and the tapped filling rate being calculated to be 0.74.
[0094] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.123, and the porosity of the model was 0.6%. The properties are shown in Table 1.
[0095] [Example 7] Mixed particles were prepared in the same manner as in Example 1, using 1200 g of the prepared particles 2, 400 g of particles 4, and 4.8 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 54 μm and 15 μm. The sphericity of the mixed particles was 96. The bulk density of the mixed particles was measured and found to be 0.70 in apparent bulk density and 0.85 in tap bulk density, with the Hausner ratio calculated from these being 1.21, and the tap filling rate was calculated to be 0.75.
[0096] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.124, and the porosity of the model was 0.5%. The properties are shown in Table 1.
[0097] [ Comparative Example 4 ] Mixed particles were prepared in the same manner as in Example 1, using 1500 g of the prepared particles 2, 250 g of particles 3, and 5.3 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 54 μm and 23 μm. The sphericity of the mixed particles was 93. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.65 and a tapped bulk density of 0.79, with the Hausner ratio calculated from these being 1.22 and the tapped filling rate being calculated to be 0.70.
[0098] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.118, and the porosity of the model was 1.1%. The properties are shown in Table 1.
[0099] [ Comparative Example 5 ] Mixed particles were prepared in the same manner as in Example 1, using 1200 g of the prepared particles 7, 400 g of particles 6, and 4.8 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 92 μm and 35 μm. The sphericity of the mixed particles was also 92. The bulk density of the mixed particles was measured and found to be 0.60 in apparent bulk density and 0.74 in tap bulk density, with the Hausner ratio calculated from these being 1.23 and the tap filling rate calculated to be 0.65.
[0100] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.115, and the porosity of the model was 1.3%. The properties are shown in Table 1.
[0101] [ Comparative Example 6 ] Mixed particles were prepared in the same manner as in Example 1, using 1200 g of the prepared particles 6, 400 g of particles 5, and 4.8 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 35 μm and 10 μm. The sphericity of the mixed particles was 94. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.55 and a tapped bulk density of 0.73, with the Hausner ratio calculated from these being 1.33 and the tapped filling rate being calculated to be 0.65.
[0102] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. Slight roughness of the powder surface was observed during the modeling process, but it was not enough to hinder the modeling. The density of the obtained model was 1.115, and the porosity of the model was 1.3%. The properties are shown in Table 1.
[0103] [Comparative Example 1] Mixed particles were prepared in the same manner as in Example 1, using 1200 g of the prepared particles 1, 400 g of particles 6, and 4.8 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 70 μm and 35 μm. The sphericity of the mixed particles was 94. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.54 and a tapped bulk density of 0.67, with the Hausner ratio calculated from these being 1.24 and the tapped filling rate being calculated to be 0.59.
[0104] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. The powder spread during the modeling was good, and no roughness of the powder surface was observed. The density of the obtained model was 1.110, and the porosity of the model was 1.8%. The properties are shown in Table 1.
[0105] [Comparative Example 2] Mixed particles were prepared in the same manner as in Example 1, using 1000 g of the prepared particles 2 and 1000 g of the particles 4, and 6.0 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) having an average particle size of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 54 μm and 15 μm. The sphericity of the mixed particles was 93. The bulk density of the mixed particles was measured and found to have an apparent bulk density of 0.44 and a tapped bulk density of 0.72, with the Hausner ratio calculated from these being 1.64 and the tapped filling rate being calculated to be 0.64.
[0106] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Co., Ltd. However, the powder compatibility was poor, and the powder surface became rough during the modeling process, so the modeling was interrupted midway.
[0107] [Comparative Example 3] Two types of particles with mode diameters of 97 μm and 40 μm were prepared by freeze-pulverizing nylon 6 (CM1010) manufactured by Toray Industries, Inc., respectively. The mixed particles were prepared in the same manner as in Example 1, using 1200 g and 400 g of the nylon 6 and 9.6 g of trimethylsilylated amorphous silica (X-24-9500 manufactured by Shin-Etsu Chemical Co., Ltd.) with an average particle diameter of 170 nm as a lubricant. The volume-based particle size distribution of the obtained mixed particles was measured and found to be bimodal, with the particle sizes of the respective peaks being 95 μm and 43 μm. The sphericity of the mixed particles was 68. The bulk density of the mixed particles was measured and found to be 0.54 in apparent bulk density and 0.67 in tap bulk density, with the Hausner ratio calculated from these being 1.47 and the tap filling rate calculated to be 0.50.
[0108] Using 1500g of this mixed particle, a three-dimensional object was manufactured using a powder bed fusion device (RaFaEl ΙΙ 150C-HT) manufactured by Aspect Corporation. Powder surface roughness was confirmed during the manufacturing process. The density of the obtained object was 1.093, and the porosity of the object was 3.3%. The properties are shown in Table 1.
[0109] [Table 1]
[0110] [Table 2]
Claims
1. Thermoplastic resin particles, characterized in that the thermoplastic resin particles are spherical and have a D50 particle size of 10 μm or more and 100 μm or less, have a bimodal volumetric particle size distribution, and when the mode diameter of the larger peak in the volumetric particle size distribution is S1 and the mode diameter of the smaller peak is S2, S2 / S1 is 0.10 or more and 0.45 or less, and have a tap filling factor, which is a value obtained by dividing the tap density of the thermoplastic resin particles by the true density of the resin constituting the thermoplastic resin particles, of 0.72 or more and 0.9 or less.
2. The thermoplastic resin particles according to claim 1, characterized in that the mode diameter S1 of the larger peak of the particle diameter distribution on a volume basis is 40 μm or more and 120 μm or less, and the mode diameter S2 of the smaller peak of the particle diameter distribution on a volume basis is 5 μm or more and 40 μm or less.
3. 3. The thermoplastic resin particles according to claim 1, wherein a Hausner ratio, which is a value obtained by dividing the tapped bulk density by the apparent bulk density, is 1 or more and 1.5 or less.
4. The thermoplastic resin particles according to claim 1 , wherein the D10 particle size is 1 μm or more and 30 μm or less.
5. The thermoplastic resin particles according to claim 1 , wherein the D90 particle size is from 50 μm to 120 μm.
6. 6. The thermoplastic resin particles according to claim 1, wherein the resin constituting the thermoplastic resin particles is a polyamide.
7. 6. The thermoplastic resin particles according to claim 1, having a sphericity of 94 or more.
8. The thermoplastic resin particles according to any one of claims 1 to 7, characterized in that the resin constituting the thermoplastic resin particles is at least one selected from polyamide 6, polyamide 12, polyamide 66, polyamide 1010, polyamide 1012, polyamide 1212, polyamide 46, polyamide 6T, and polyamide 6I, or a copolymer thereof.
9. 9. The thermoplastic resin particles according to claim 1, which are used for producing a three-dimensional object by powder bed fusion.
10. A method for producing a three-dimensional object by powder bed fusion bonding using the thermoplastic resin particles according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for additive manufacturing of parts by selective melting or selective sintering of an optimized powder bed using a high energy beam
JP2016505415A
Powder for molding
JP2017127998A
Powder for solid molding, resin powder, and manufacturing method of solid molded article
JP2019084815A
Powder for solid forming, resin powder, production apparatus of solid form, and production method of solid form
JP2019084816A
Resin powder, resin powder for three-dimensional molding, three-dimensional molding, method for producing three-dimensional molding, and device for producing three-dimensional molding
JP2020189965A